Pendekatan Berdiferensiasi dan Dampaknya terhadap Kemampuan Penalaran Matematis SMK Negeri 1 Tolitoli - Mulyana, Anna; Yumiati; Susandi, Ardi Dwi (LPPM Universitas Madako Tolitoli, 2025)
This study aims to analyze the impact of differentiated instruction on students' mathematical reasoning abilities at SMK Negeri 1 Tolitoli. The background of the study lies in the low level of students’ mathematical reasoning skills, which is attributed to uniform teaching methods that overlook students' varying characteristics. A quasi-experimental method was employed using a Non-random Pre-test Post-test Control Group design. The sample consisted of two classes from the Accounting and Financial Institution program and two classes from the Computer and Network Engineering program, each divided into experimental and control groups. Research instruments included mathematical reasoning tests and observation sheets. Statistical analysis revealed that differentiated instruction had a significant positive effect on students’ mathematical reasoning abilities compared to conventional teaching approaches. The independent sample t-test indicated significant differences in post-test scores between the experimental and control groups in both vocational programs. These findings suggest that differentiated instruction is effective in enhancing mathematical reasoning skills among vocational school students and can serve as an adaptive and contextual teaching strategy.